Computational insight into the phthalocyanine-DNA binding via docking and molecular dynamics simulations - MUTLU, ÖZAL; ERDEM, SAFİYE (ELSEVIER SCI LTD, 2018)
Phthalocyanines are considered as good DNA binders, which makes them promising anti-tumor drug leads. The purpose of this study is to investigate the interactions between DNA and quaternary metallophthalocyanine derivatives (Q-MPc) possessing varying metals (M = Zn, Ni, Cu, Fe, Mg and Ca) by molecular docking since there seems to be a lack of information in the literature regarding this issue. In this direction, Autodock Vina and Molegro Virtual Docker programs were employed. Autodock Vina results reveal that each Q-MPc derivative binds to DNA strongly with similar binding energies and almost identical binding modes. They bind to the grooves of DNA by constituting favorable interactions between phosphate groups of DNA and Q-MPcs. Although changing the metal has no significant effect on binding, presence of quaternary amine substituents increases the binding constant K-b by about 2-fold comparing to the core Pc (ZnPc). Contrary to Autodock Vina, the calculated Molegro Virtual Docker binding scores have been more diverse indicating that the scoring function of Molegro is better in differentiating these metals. Despite the fact that Molegro is superior to Autodock Vina in terms of metal characterization, Autodock Vina and Molegro exhibit similar binding sites for the studied metallophthalocyanines. We propose that Q-MPc derivatives designed in this study are promising anti-tumor lead compounds since they tightly bind to DNA with considerably high K-b values. Cationic substituents and presence of metal have both positive effects on DNA binding which is critical for designing DNA-active drugs. Additional calculations employing molecular dynamics (MD) simulations verified the stability of Q-MPc-DNA complexes which remained in contact after 20 ns via attractive interactions mainly between DNA backbone and the Pc metal center.
Keywords: Docking; Binding affinity; Drug design; Molecular modelling; Autodock Vina; Molegro Virtual Docker; FREE-ENERGY; CATIONIC PHTHALOCYANINES; BASE-PAIRS; COMPLEXES; HETERODIMERIZATION; OPTIMIZATION; ALGORITHM; ACCURACY; ZINC(II)